Makan-makan Dalam Kelambu; Diversity of Malay-Bugis Tradition in Pontianak West Kalimantan - Sri Retno, Elza (Khatulistiwa, 2018)
This article forms the results of a study conducted by the author in an effort to be able to inform the culture of Bugis tribe tradition, which is trusted and carried out with an expectation for the benefit of a better life. The culture possessed by Bugis people in the equatorial city is very diverse, in each sub-district even has its own differences. Makan-makan in Kelambu which was carried out in West Pontianak District which was a very densely populated location of Malay-Bugis. More clearly the location is in Kelurahan Sungai Jawi Dalam, Jalan Srikaya. It was here that at that time had carried out a cultural activity called Makan-makan dalam Kelambu. This tradition is carried out by people who do celebrations and are carried out by Bugis people in general. But at that time the people who carried out the celebration were not only the original Bugis tribe, but also a mixture of Bugis Malay tribes. This is what Malay-Bugis people do in Makan-makan dalam Kelambu tradition. The tradition of Makan-makan Dalam Kelambu is a series of activities that are believed by Malay-Bugis community to be carried out for safety and a form of gratitude to the Almighty God and avoid supranatural spirit disorder.